PERAN PEMBELAJARAN DALAM MEMBENTUK KARAKTER BERTANGGUNG JAWAB SOSIAL SISWA SEKOLAH DASAR - Aulia Zulfa; Ersipa Anjelina; Mulia; Inda Dwi Aulia; Herliah; Dine Trio Ratnasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article aims to examine and explore the role of social studies education in shaping students' sense of social responsibility. This study adopts a qualitative approach with a descriptive method, where the theories discussed are derived from various literature reviews, including journals, articles, and books written by experts in relevant fields. Character is the accumulation of values practiced in daily life, becoming a lasting quality for an individual. Social studies education plays an important role in shaping the character of the Indonesian nation, as it aligns with character development. Both aim to enable students to act as good citizens, be concerned about social and environmental issues around them, and foster a strong sense of nationalisme.